The Importance of Immunohistochemical Analysis in Silent Pituitary Adenoma - Harsono, Ivan William; Stevina, Nathania Victoria; Puspitasari, Vivien; July, Julius (Medicinus, 2017)
Pituitary adenoma contributes to 15% of all intracranial neoplasm. It is usually following benign course and some of them are silent (asymptomatic clinically, but hormone-secreting). Silent adenoma usually found incidentally or when the patients show mass effect (neurological deficits). Many of histologically aggressive silent adenoma subtypes are associated with invasiveness, recurrence and progression to clinically functioning adenomas. Aggressive silent adenoma radiologically tends to invade in downward direction, invading bone, sinus cavernosus, parasellar region. The nature of aggressive silent adenoma subtypes is differing in nature compared to benign nature of pituitary adenoma and should be confirmed immunohistochemically to determine the prognosis and anticipate the risk of recurrence or progression. The case illustration show a real case of 46 years old female progressive headache and visual disturbance diagnosed with non-functional pituitary macroadenoma but positive for more than one immunochemistry biomarker (plurihormonal aggressive silent adenoma).